2017
DOI: 10.1021/acsami.7b11681
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Self-Assembled Nanostructures with Distinct Morphologies and Properties Fabricated by Molecular Design

Abstract: Six surfactant-like peptides with the same amino acid composition but different primary sequences are designed, including GAVIK, KIVAG, IVAGK, KGAVI, VGIAK, and KAIGV. These peptides form antiparallel β-sheets during self-assembly. Because the constituent residues have different side chain size and hydrophobicity, sequence changes adjust group distribution and hydrophobicity on the two sides of a given β-sheet. This consequently tunes the binding energy of the side-to-side pairing conformations and leads to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 61 publications
4
37
0
Order By: Relevance
“…This result indicates that the neighboring sequence of an amyloid‐core affects the thermodynamic stability of the resulting assemblies, as previously observed for barnase‐related peptide fibrils . We also evaluated the critical aggregation concentration (CAC) of KI 10 using pyrene, a probe that is sensitive to the polarity of the local environment . A sharp transition from monomers to assemblies was observed when the concentration exceeded 33 × 10 −6 m (Figure d, Figure S7, Supporting Information).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…This result indicates that the neighboring sequence of an amyloid‐core affects the thermodynamic stability of the resulting assemblies, as previously observed for barnase‐related peptide fibrils . We also evaluated the critical aggregation concentration (CAC) of KI 10 using pyrene, a probe that is sensitive to the polarity of the local environment . A sharp transition from monomers to assemblies was observed when the concentration exceeded 33 × 10 −6 m (Figure d, Figure S7, Supporting Information).…”
Section: Resultssupporting
confidence: 64%
“…CAC was determined by plotting the ratio of fluorescence intensity (373 nm/384 nm) as function of the concentration. Intersection of the two linear fits was used to determine the CAC …”
Section: Methodsmentioning
confidence: 99%
“…toward the size distribution of the oligomeric particles and the thermodynamic stability of the fibrils are also evaluated, which helps defining the mechanism leading to the differential polymerization yield. Thereby, our study enhances our understanding of the important role of oligomeric intermediates in defining the outcome of self-assembly systems and advances the rational design principles of self-assembling peptides that give different supramolecular properties for a wide latitude of applications [2][3][4]44,45 . Moreover, our findings suggest that charged protein gatekeeper sequences 46 can prevent amyloidosis by lowering the size of the oligomeric particles.…”
Section: Resultsmentioning
confidence: 78%
“…In contrast, for applications that require the fibril infrastructure, e.g., for therapeutic scaffolds [2][3][4] , one should engineer the SLP with higher β-sheet propensities and lower number of charges to maximize the yield of fibril structures (like SLP1). In addition, for applications that use 1D nanofibers as reservoir for hydrophobic drug release 45 , the amount of micellar oligomer co-present in the system can affect the overall drug release profile. At last, with respect to protein aggregation, a previous genome-wide sequence analysis revealed that, in close proximity to the aggregation-prone β-strand regions in proteins, charged ''gatekeeper" residues often prevent the β-strand sequences from aggregating 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Short amphiphilic peptides are one important category of self-assembling peptides that can form distinct nanostructures [36,37]. By having specific mechanistic property and high biocompatibility, these nanostructures show potential applications in vast areas including templates for nanostructure construction [38], scaffolds for tissue engineering [39,40], carriers for medicine delivery [41,42,43], and biological surface engineering [44,45]. It is of great interest to see whether we can develop temperature-responsive self-assembly molecules by involving the elastin β-turn units into the amphiphilic peptides.…”
Section: Introductionmentioning
confidence: 99%